Constructing the enemy in the process of virtue signalling: A critical reflexion on media representations of Jordan Peterson - Tomoiaga, Ligia (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2024)
This article depicts an analysis of the media production of a controversial figure, Canadian professor and clinical psychologist Jordan Peterson, as a fragment of popular culture. Based on the methods of literary criticism and on the comparison, interpretation of themes and style, with the support of images and wordings circulating in the media, the proposed critical reflection does not concern his ideas, but how the media influenced their audiences by creating an enemy through their representations of this public intellectual. The text is an attempt by the author, who lived under a totalitarian communist regime, to demonstrate how propaganda techniques, such as virtue signalling, stigmatize.